Rent-sharing e desigualdade salarial intrafirma - Assis, Carolina,Corseuil, Carlos Henrique,Freguglia, Ricardo da Silva (Instituto de Pesquisa Econômica Aplicada, 2019)
This study investigates the effects of changes in firms' performance on wages across occupations from the extractive and transformation sectors of the Brazilian economy, from 2007 to 2013. We rely on a matching panel data of occupations and industries using data from a Brazilian Administrative File (RAIS) and a Survey of Manufacturing Firms (PIA-Empresa). The estimation strategy we propose involves the control of the unobserved heterogeneities of the occupation-firm cell. One advantage of our identification strategy is to not depend on the hypothesis that workers move between companies for exogenous reasons. The results point to the existence of a positive and significant relationship between firm performance and wages, as well as the existence of greater appropriation of performance improvements by management positions. The estimated coefficients, however, suggest elasticities lower than those reported for developed countries.
10419/240729
Keywords: Graue Literatur; rent-sharing; wages; occupations